Peningkatan Millenial Anti Bokek melalui capital market investment for beginners pada Siswa MAN 2 Magetan - Fitria, Fitria; Ubaidillah, Moh. (Nur Science Institute, 2022)
The low-middle economic family background makes the welfare of MAN 2 Magetan students far from qualified. The condition of students who are still in school and do not have the skills to make students unable to become freelancers. This community service activity aims to provide alternative solutions to student problems by providing knowledge and assistance regarding capital market investment so that students can get additional pocket money. The essence of this community service activity is the contribution in overcoming the mission, which is the implementation of the first SDG points. The implementation of this activity uses the blended meeting method, namely webinars (online) and training and direct assistance (offline). The results of this community service activity indicate an increase in knowledge and awareness of the urgency of capital market investment, as evidenced by the pre-test and post-test results on 24 participants. The evaluation results of the average value before the activity was 32.08, and after the activity became 62.08. Another result is skills regarding mutual fund stock trading.